The intertextualistic phenomenon in preeti shenoy’s life is what you make it, it happens for a reason and a hundred little flames - Pandeeswari, D.; Hariharasudan, A.; Nawaz, Nishad (Linguistics and Culture Review, 2021)
Postmodern intertextuality abbreviates the relation between the texts that has related to incidents, quotes, allusions, translation and so on. The aim of the study accolades on the postmodern tendency of intertextuality in Preeti Shenoy’s selected texts, Life is What You Make It, It Happens for a Reason and A Hundred Little Flames. Preeti Shenoy is a multifarious postmodern writer. The term intertextuality has linked with other texts. The features of intertextuality are quotation, scenes, characters, narration, allusion etc. The notable theorists of intertextuality are Julia Kristeva, Roland Barthes and Mikhail Bakhtin, and the present study has adopted the intertextual concepts from the considered theorists. The methodology of the study splits into four intertextual concepts – description of a word, different circumstances link, language and dialogue. The first two concepts, proposed by Julia Kristeva, are description of a word and different circumstances link. Roland Barthes has proposed the intertextual concepts of language and dialogue. Mikhail Bakhtin also has proposed the intertextual concept of language. These intertextual concepts are adopted in the present study, and the authors have investigated the intertextual elements in the select texts of Shenoy.